A marriage of convenience the New Zionist Organization and the Polish Government ; 1936 - 1939 - Weinbaum, Laurence (Columbia Univ. Press u.a., 1993)
Chronicles the relationship between the revisionist Zionist movement, as reflected by the New Zionist organization (Nzo), and the Polish government.
Keywords: Zʹaboṭinsḳi, Zeʾev -- 1880-1940; New Zionist Organization -- History; New Zionist Organization; Polen -- Rada Ministrów; Geschichte 1936-1939; Organisaties; Overheidsbeleid; Zionisme; Geschichte; Politik; Zionism -- Poland; Zionismus; Polen; Poland -- Politics and government -- 1918-1945; Poland -- Ethnic relations